Eğitim tipi CNC frezesinin tasarımı ve imalatı - Özdeveci, Murat (My University, 2001)
Yirminci asrın ikinci yarısında insan, tüm tarih boyunca görülmeyen bir ilerleme kaydetmiştir. İcat edilen her türlü araç-gereci kullanarak hayat standardını iyileştirmeye ve yükseltmeye çalışmıştır. CNC tezgahlar bu yüzyılda en önemli icatlardam birisidir. M.I.T (Massachusetts Institue of Technology), 1952 yılında A.B.D. Hava Kuvvetleri için karışık parçaların seri üretimi için ilk sayısal denetimli tezgahı geliştirdi. Mikroişlemcilerin gelişmesi üzerine NC makinaların üretimi büyük oranda arttı. Yüksek kesme kapasitesi, hassas hız, daha uzun ömür, CNC makinaların atelye ve fabrikalardaki sayısını arttırdı. Fakat bu da NC konusunda yetişmiş personel ihtiyacı doğurdu. Bu yüzden NC eğitimi okulda ve sanayide büyük öneme sahiptir. Tez çalışmamda eğitim ve alıştırma amaçlı bir takım tezgahı tasarladım ve imal ettim. Bilgisayar denetimli olduğundan daha önce bilgisayarla kumandayla tanışmamış olanlar için iyi bir fırsat olacaktır. Tezgah, Pascal, C ve Delphi gibi programlama dilleri ile adım adım programlanır. Öğrenci programını makinaya yükler ve sonucunu hemen tezgahta görebilir. Bu da öğrenciyi birçok kuru ve teorik bilgilerden kurtaracaktır. Öğrencinin talaş kaldırma işlemlerini daha iyi anlamalarını sağladığı gibi iş için uygun takım ve alet seçme yeteneğini geliştirir. Tez danışmanım Yrd. Doç. Dr. Hasan Tahsin KALAYCI'ya değerli önerilerinden, Seçkin AKSU'ya imalatta ve İsmail KUŞ'a tezin yazımında yardım etmelerinden dolayı te-şekkürü bir borç bilirim.

The humanbeing in the second half of the 20th century has recorded a progress which hasn't been seen along all the history. He has tried to heal and increase the life standard by using every kind of equipment being invented. Computerized Numerical Control(CNC) uses a computer to instruct a machine tool to what dimensions and how to produce a machining part. CNC can be used on any type of machine tool including milling machines, lathes, grinders and laser cutting machines. CNC machine is one of the most important inventions in this century. In 1952, Pearson Inc. and the M.I.T. (Massachusetts Institute of Technology) developed the first numerically controlled machine tool for the production of particularly complicated workpieces on behalf of the United States Air Force. By reason of the development of the microprocessor, the production of the NC machines grew enor-mously. Higher cutting capacity, precision speed, longer life have increased the number of CNC machines in workshops and factories. But these advantages have involved high demand for NC-trained personel. Therefore training is of utmost importance in school and industry. I have designed and built a machine tool for educational and training purposes in my thesis study. It has a computerized control for those who has never dealt with computers before, and this will be an opportunity for some students to get acquainted with computer. The machine's table that is driven by step motors has two movements, longitudinal(away and towards us) with 80 mm and horizontal (side from side) with 250 mm. Cutting tool moves a vertical movement with 150 mm. The machine is programmed step by step with programming languages such as Pascal, C, Delphi. Then the student puts the program immediately into the machine and see the result right away. And this will save him many dry, theoretical lessons. It enables the students to understand machining technology better and strengthens their ability to choose proper fixture and tooling system.
Keywords: Cnc Tezgahları Takım Tezgahları; Makine Eğitimi